Cloud learning technology: an attempt to define - O. M. Markova (Academy of Cognitive and Natural Sciences, 2014)
Objectives of the study: to give a definition of cloud learning technology as a computer-oriented component of educational technology. Research objectives: 1) to form definition of cloud learning technology; 2) to clarify the relations of cloud learning technology, educational technologies, ICT, cloud technologies and ICT of learning. Object of study: cloud technology in education. Research subject: cloud learning technology. Methods: source analysis, definition synthesis. Research results: a definition of cloud learning technology was given; the relations of cloud learning technology, educational technologies, ICT, cloud technologies and ICT of learning was given. Conclusions and recommendations: 1) the content of cloud learning technology is the intersection of sets of concepts related to cloud technology and ICT-based learning; 2) further development of research involves determining the historical and pedagogical conditions of emerging and development of cloud learning technology.